PENGARUH LIQUIDITY, LEVERAGE DAN FIRM SIZE TERHADAP FINANCIAL DISTRESS - Rahardjo, Christie; Nariman, Augustpaosa (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The purpose of this study is to determine the influence of liquidity, leverage and frm size on financial distress studies on non-financial companies listed on the Indonesia Stock Exchange (IDX) in the period of 2018 -2020. The sampling method uses as many as 34 samples of non-financial companies that have been re-selected with a total of 102 data for a three-year period. Then this study used secondary data. The data processing in this study used eviews version 12 software. The results of this study show that liquidity does not affect financial distress and then leverage and firm size have a negative effect on financial distress.